Varāhamihira’s Physiognomic Omens in the Garuḍapurāṇa - Zysk, Kenneth G. (History of Science in South Asia, 2019)
In this paper, I study the three chapters devoted to human physiognomy in the Garuḍapurāṇa. Two of the three come directly from Varāhamihira’s sixth-century Bṛhatsaṃhitā with the commentary (vivṛti) of the Kaśmirian Bhaṭṭotpala (fl. ca. 966 or 969 CE). I hope to make two research contributions. First, I hope to show that the date of this section of the Purāṇa, if not indeed the entire Purāṇa, cannot be before the sixth century and probably after the tenth century. Second, I will illustrate how a text in different metres was normalised into anuṣṭubh metre for ease of memory and recitation. I shall conclude with a discussion of the lessons we can learn from this kind of ancient Indian redaction process